Analisis Deskriptif tentang Strategi Mutu Pelayanan Kandungan (Obstetri dan Ginekologi) di Rumah Sakit Islam NU Demak - Safi’i, Akhmad; Aziz, Abdul (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Demak Regency are still high. In 2023, the MMR was 13 cases or 67 per 100,000 live births with a delivery rate of 18,784. The 2023 IMR data reached 7.2 per 1000 live births. The still high MMR and IMR and the socio-cultural market conditions of Demak, which are religious, are very relevant to the need for integrated superior services. Especially in Obgyn, perinatal, and child services. The Islamic Hospital (RSI) NU Demak is present through comprehensive, superior Obgyn services with a trend in patient visits that continues to increase in 2023. This study determined the strategies the Management of RSI NU Demak implemented to improve patient visits to Obgyn services. The study was conducted qualitatively using a case study approach. Data collection techniques through observation, documentation, and Focus Group Discussion (FGD). Patient visit data was taken from January – May 2023. The results showed that the success factors for increasing the number of patient visits were human resources, facilities and infrastructure, external networks, marketing team strategies, and positioning of RSI NU Demak. Efforts that can be made to increase patient visits are recruiting female Obgyn specialist doctors to fill the empty doctor's schedule slotting time and implementing other cutting-edge methods that are not yet available in Obgyn service activities.